Early life factors associated with childhood trajectories of violence among the Birth to Twenty-Plus Cohort in Soweto, South Africa - Lilian Muchai; Sara Naicker; Juliana Kagura (PLoS ONE, 2025)
Violence against children (VAC) has devastating and long-term negative consequences on health, social and economic well-being at both the individual and societal levels. There is limited research on the life course experience of VAC, especially in Africa. This study aimed to identify trajectories of physical and sexual violence victimization in childhood and evaluate early life factors predicting these violence trajectories. This study used data from birth to 18 years from the ongoing prospective Birth to Twenty Plus cohort (Bt20+). Analyses included children who reported experiences (yes/no) of physical and sexual violence at a minimum of two time points between five and 18 years. Group-based trajectory modelling was employed to identify groups of children with similar patterns of violence over time, while multivariable logistic regression was used to establish early life factors associated with violence trajectory group membership. Separately, two trajectory groups of physical violence ( adolescent limited (65.1%) and chronic increasing (34.9%)) and sexual violence ( adolescent limited (74.1%) and late increasing (25.9%)) victimization were identified. Early life factors associated with a higher risk of chronic increasing trajectory group membership, after adjusting for covariates, were being male (adjusted odds ratio [aOR] 1.67, 95% CI 1.31; 2.10) and having a mother with at least secondary education compared to higher education (aOR 1.73, 95% CI 1.08; 2.76). In addition, residing in middle, compared to low, socioeconomic households (aOR 0.68, 95% CI 0.50; 0.92) was protective against membership in this group. Residing in high compared to low socioeconomic households, was the only early life factor whose association approached significance with membership in the late-increasing sexual violence victimization trajectory group (aOR 0.63, 95% CI 0.42; 0.95). In conclusion, children follow different violence victimization trajectories across their childhoods. Identifying early life factors predicting violence trajectories provides targeted prevention intervention areas that can mitigate children’s violence experience.